2003
DOI: 10.1097/01.prs.0000086140.49022.ab
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering Skin Flaps: Which Vascular Carrier, Arteriovenous Shunt Loop or Arteriovenous Bundle, Has More Potential for Angiogenesis and Tissue Generation?

Abstract: This study was designed to clarify which vascular carrier, the arteriovenous shunt loop or the arteriovenous bundle, has more potential as a vascular carrier for an artificial skin flap in rats. An arteriovenous shunt loop was constructed between the femoral artery and vein using an interpositional artery (group I) or vein (group II) graft. For arteriovenous bundle groups, the femoral artery and vein were used and subdivided into two groups: distal ligation type (group III) and flow-through type (group IV). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(112 citation statements)
references
References 22 publications
2
104
0
6
Order By: Relevance
“…The model was enhanced by Morrison and coworkers who inserted the loop into isolation chambers resulting in a successful vascularisation of polymer-and gel matrices [11,17]. This group also demonstrated the superiority of the AV loop as vascular carrier in comparison to the vascular bundle in terms of vascular density and capacity for generation of new tissue [18]. Based on these findings we decided to generate AV loops for induction of vascularisation instead of the distally ligated femoral pedicle (as used by Birla and coworkers [13]), though microsurgical preparation of the loop is far more challenging and meticulous.…”
Section: Discussionmentioning
confidence: 97%
“…The model was enhanced by Morrison and coworkers who inserted the loop into isolation chambers resulting in a successful vascularisation of polymer-and gel matrices [11,17]. This group also demonstrated the superiority of the AV loop as vascular carrier in comparison to the vascular bundle in terms of vascular density and capacity for generation of new tissue [18]. Based on these findings we decided to generate AV loops for induction of vascularisation instead of the distally ligated femoral pedicle (as used by Birla and coworkers [13]), though microsurgical preparation of the loop is far more challenging and meticulous.…”
Section: Discussionmentioning
confidence: 97%
“…The mean thickness of compact cardiac tissue is similar to that of the adult rat right ventricular wall, 41 is many times larger than all heart tissues engineered in vitro to date, 4,5,8 -10 and is comparable to the thickness attained by polysurgery of cell sheet grafts. 14 This approach has recently been adopted in the flow-through pedicle model, 42 which is less angiogenic than the AV loop model, 43 which perhaps explains why up to 20 million cells generated only small amounts of tissue. 42 The concept of tissue engineering in situ with a dedicated blood supply permits the implanted cells, aided by the invasion of inflammatory cells, fibroblasts, and endothelial cells, to orchestrate their own endogenous cascade of appropriate cytokines, chemokines, and matrix production.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the arterovenous loop enhanced neovascularization in a higher degree than an arteriovenous shunt. 23 The Teflon isolation chamber prevents the scaffolds from extrinsic vascularization from the surrounding tissue. 24 Therefore, the constructs are exclusively vascularized from the vascular axis.…”
Section: Discussionmentioning
confidence: 99%